Respostas
respondido por:
0
x + 4 6
---------- = -------
x + 1 x - 1
( x - 1 ) ( x + 4 ) = 6 ( x + 1 )
x² + 4x - x - 4 = 6x + 6
x² + 3x - 6x - 4 - 6 = 0
x² - 3x - 10 = 0
x = 3 + -√9 + 40
-----------------
2
x = 3 + -√49
------------
2
x' = 3 + 7
----------
2
x' = 5
x" = 3 - 7
--------
2
x" = - 2 Não Serve.
Perímetro = x + 4 + x + 1 + 6 + x - 1 + 15
5 + 4 + 5 + 1 + 6 + 5 - 1 + 15 = P
P = 40 cm Resposta.
---------- = -------
x + 1 x - 1
( x - 1 ) ( x + 4 ) = 6 ( x + 1 )
x² + 4x - x - 4 = 6x + 6
x² + 3x - 6x - 4 - 6 = 0
x² - 3x - 10 = 0
x = 3 + -√9 + 40
-----------------
2
x = 3 + -√49
------------
2
x' = 3 + 7
----------
2
x' = 5
x" = 3 - 7
--------
2
x" = - 2 Não Serve.
Perímetro = x + 4 + x + 1 + 6 + x - 1 + 15
5 + 4 + 5 + 1 + 6 + 5 - 1 + 15 = P
P = 40 cm Resposta.
Perguntas similares
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás